2020
DOI: 10.3390/jcm9041009
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Results of Soft Tissues around a New Implant Healing-Abutment Surface: A Human Study

Abstract: Although, the high success rate of implant rehabilitation treatment, the biological complications such as bone loss and peri-implantitis are still present. The creation of a coronal biological seal between the implant and the oral tissues seems to be a crucial point on preserving dental implants. The objective of this study was to immunohistochemically analyze the behavior of peri-implant soft tissues around a new implant healing-abutment surface on humans. A total of 30 soft tissue biopsies were collected aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 51 publications
1
28
0
1
Order By: Relevance
“…The general inflammatory status that affect the gingival epithelium leads also to the increase in CK-18 and CK-19 expression, in line with previous studies that showed the overexpression of these two cytokeratins in junctional epithelium flogosi [ 45 , 46 ] and high positivity of CK19 in the epithelium inside the periodontal pocket and in the inflamed gingival epithelium [ 22 ]. Moreover, CK-19 expression is known to be directly proportional to the degree of proliferative activity and inversely proportional to E-cadherin [ 47 , 48 ]: accordingly, it has already been reported that E-cadherin levels are dramatically downregulated in the epithelium surrounding the machined titanium surfaces [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The general inflammatory status that affect the gingival epithelium leads also to the increase in CK-18 and CK-19 expression, in line with previous studies that showed the overexpression of these two cytokeratins in junctional epithelium flogosi [ 45 , 46 ] and high positivity of CK19 in the epithelium inside the periodontal pocket and in the inflamed gingival epithelium [ 22 ]. Moreover, CK-19 expression is known to be directly proportional to the degree of proliferative activity and inversely proportional to E-cadherin [ 47 , 48 ]: accordingly, it has already been reported that E-cadherin levels are dramatically downregulated in the epithelium surrounding the machined titanium surfaces [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported through histological findings that the gingiva adherent to this new laser-treated surface keeps a regular morphology in all its parts, while the region of the gingiva adherent to the machined surfaces shows several stress hallmarks, including highly inflamed areas with neutrophilic infiltration [ 8 ]. The authors concluded that the use of laser-treated surface on healing abutment could positively influence the healing of peri-implant soft tissues and it is preferable to maintain the integrity and functionality of the gingiva epithelium.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations